Microbial ecology of mountain glacier ecosystems: biodiversity, ecological connections and implications of a warming climate. (30th May 2017) - Hotaling, Scott; Hood, Eran; Hamilton, Trinity L.
Summary: Glacier ecosystems are teeming with life on, beneath, and to a lesser degree, within their icy masses. This conclusion largely stems from polar research, with less attention paid to mountain glaciers that overlap environmentally and ecologically with their polar counterparts in some ways, but diverge in others. One difference lies in the susceptibility of mountain glaciers to the near‐term threat of climate change, as they tend to be much smaller in both area and volume. Moreover, mountain glaciers are typically steeper, more dependent upon basal sliding for movement, and experience higher seasonal precipitation. Here, we provide a modern synthesis of the microbial ecology of mountain glacier ecosystems, and particularly those at low‐ to mid‐latitudes. We focus on five ecological zones: the supraglacial surface, englacial interior, subglacial bedrock–ice interface, proglacial streams and glacier forefields. For each, we discuss the role of microbiota in biogeochemical cycling and outline ecological and hydrological connections among zones, underscoring the interconnected nature of these ecosystems. Collectively, we highlight the need to: better document the biodiversity and functional roles of mountain glacier microbiota; describe the ecological implications of rapid glacial retreat under climate change and resolve the relative contributions of ecological zones to broader ecosystem function.